Inovasi Pembelajaran PAI Berbasis Teknologi: Menjawab Tantangan Era Society 5.0 - Dea Astuti; Indah Permata Sari; Mukmin Mukmin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The Society 5.0 era requires Islamic Religious Education (IRE) to adapt and transform through the application of technology, enabling it to respond to the needs of students living in the midst of digital developments. Various obstacles, such as limited digital competence of teachers, unequal access to technology, and low religious digital literacy, demonstrate the importance of more contextual and flexible IRE learning innovations. This study aims to identify forms of technology-based learning innovation, analyze barriers to its implementation, and formulate effective strategies for integrating technology to address challenges in the Society 5.0 era. The research method used is a literature study reviewing various scientific sources, such as journals, books, articles, and online literature published in the last ten years. Thematic content analysis techniques were used to reveal patterns, main issues, and relationships between themes in the process of digitizing PAI learning. The results of the study show that the use of various digital media, such as e-learning platforms, educational Islamic applications, interactive media, learning videos, and gamification systems, can increase student motivation, engagement, and understanding. In addition, digital innovation strengthens critical thinking skills through technology-assisted problem-based learning models. Curriculum updates that integrate technology ethics, blended learning, and inquiry approaches reinforce the relevance of religious education in the digital age. Thus, the application of technology in Islamic education is a strategic step toward shaping students who are spiritual, critical, adaptive, and ready to face the challenges of Society 5.0.   Keywords:  Islamic religious education, innovation in learning, digital literacy, Society 5.0 era